Immunosuppressive therapy influences the accelerated age-dependent T-helper cell differentiation in systemic lupus erythematosus remission patients - Schaier, Matthias; Gottschalk, Claudius; Uhlmann, Lorenz; Speer, Claudius; Kälble, Florian; Eckstein, Volker; Müller-Tidow, Carsten; Meuer, Stefan; Mahnke, Karsten; Lorenz, Hanns-Martin; Zeier, Martin; Steinborn-Kröhl, Andrea (Arthritis Research & Therapy, 2018)
CD4+ T cells are of great importance in the pathogenesis of systemic lupus erythematosus (SLE), as an imbalance between CD4+ regulatory T cells (Tregs) and CD4+ responder T cells (Tresps) causes flares of active disease in SLE patients. In this study, we aimed to find the role of aberrant Treg/Tresp cell differentiation for maintaining Treg/Tresp cell balance and Treg functionality.
Gesehen am 26.11.2024